Four styles of strategy development. - IDENBURG, P.J. (1993)
Identifies and examines four views of the strategy development process : rational planning, planning as a guided learning process, planning on the basis of logical incrementalism, and, emergent strategy formation. Concludes that these four views must be reflected in business research and education.